Grenada. Significant achievements 2017 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2018)
The main activities carried out by the Institute in Granada during 2017 are identified, with respect to the needs and interests of the country, strengthening issues such as family farming, innovation, sustainability, beekeeping, composting, governance and resilience against climate change. Likewise, work was done on technology, marketing and gardening. Finally, the use of organic fertilizers and the inclusion of young people in agricultural processes were supported.